Qualified Brazilian migrant women in Dubai: constraints, agency, and change in the migratory process - Motta, R. N. (2022)
In a classic capitalist society of Jewish–Christian tradition, the roles of women within the domestic sphere are those of daughter, mother, housewife, and, depending on the marital status, “dedicated” wife. Outside the home space, the role assigned to women corresponds to that of an increasingly qualified salaried person who earns less when working the same workload as men, in addition to carrying out domestic activities (Saffioti 1976). In this social context, the patriarchal framework associated with capitalism weighs down on women. It requires them to be productive outside home and to have various roles in the domestic space of social reproduction, maintaining limited social power notwithstanding the progress towards a greater gender equality evidenced over the last few decades. By internalizing all these functions within the scope of their personality considered not in an isolated but in a dynamic and contextually related way, women, namely qualified women, are influenced by the entrepreneurial context in which they work, which demands of them competitiveness and success through the use of their skills (Killian and Manohar 2016; Ryan and Mulholland 2014).